Bringing Light into the Diagnosis of Skin Disorders - Short Review on Laser Induced Fluorescence Spectroscopy and Optical Coherence Tomography in Dermatology - Ghervase, L.; Carstea, E.M.; Borisova, E.; Forsea, A.M. (Current Medical Imaging, 2014)
The study of optospectral techniques for the non-invasive, in vivo diagnosis of skin diseases has intensified in the last years. Optical diagnosis methods have already started to prove their ability to reveal specific skin functions and to identify skin lesions and their various stages, allowing for the early diagnosis of skin diseases and monitoring of their treatments. At the moment, these techniques have great inter and intra-patient variations, which could be overcome by the use of combined optical techniques, assuring greater accuracy and complementary information, and thus, entering the mainstream of medical practice. After a brief review concerning light-induced fluorescence spectroscopy (LIFS) and optical coherence tomography (OCT) methods, the article intends to present the benefits of applying a combination of both methods for improved diagnostic accuracy in the case of both benign and malignant disorders of the skin.
Keywords: fluorophores